Ciliary neurotrophic factor upregulates follistatin and Pak1, causes overexpression of muscle differentiation related genes and downregulation of established atrophy mediators in skeletal muscle - Tsompanidis, A.; Vafiadaki, E.; Bluher, S.; Kalozoumi, G.; Sanoudou, D.; Mantzoros, C.S. (MetabolismMetabolismMetabolism, 2016)
INTRODUCTION: The Ciliary Neurotrophic Factor (CNTF) is a pluripotent cytokine with anorexigenic actions in the hypothalamus that improves insulin sensitivity, increases energy expenditure and induces weight loss. Since CNTF also has an established myotrophic role, we sought to examine whether skeletal muscle contributes to the CNTF-induced metabolic improvement and identify the molecular mechanisms mediating these effects. METHODS: We used a mouse model of diet-induced obesity, to which high or low CNTF doses were administered for 7days. Whole transcriptome expression levels were analyzed in dissected soleus muscles using microarrays and data were then confirmed using qRT-PCR. RESULTS: We demonstrate that CNTF administration significantly downregulates leptin, while it upregulates follistatin and Pak1; a molecule associated with insulin sensitization in skeletal muscle. A significant overexpression of muscle differentiation related genes and downregulation of established atrophy mediators was observed. CONCLUSIONS: The overall gene expression changes suggest an indirect, beneficial effect of CNTF on metabolism, energy expenditure and insulin sensitivity, exerted by the pronounced stimulation of muscle growth, with similarities to the described effect of follistatin and the activation of the Akt pathway in skeletal muscle.
Keywords: Animals; Atrophy/metabolism; Ciliary Neurotrophic Factor/*pharmacology; Down-Regulation/*drug effects; Follistatin/genetics/*metabolism; Gene Expression Regulation/drug effects; Male; Mice; Muscle, Skeletal/drug effects/*metabolism; Obesity/*metabolism; p21-Activated Kinases/genetics/*metabolism; Up-Regulation/*drug effects